2018
DOI: 10.1007/978-1-4939-8672-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Lipases: An Overview

Abstract: Lipases are ubiquitous enzymes, widespread in nature. They were first isolated from bacteria in the early nineteenth century, and the associated research continuously increased due to the characteristics of these enzymes. This chapter reviews the main sources, structural properties, and industrial applications of these highly studied enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 151 publications
1
101
0
2
Order By: Relevance
“…Leu17 is one of the two hydrogen‐bond donor amino acid residues that constitute the BCL oxyanion hole and stabilize the tetrahedral intermediate during catalysis. As described before, the two constituent's amino acids (Leu17 and Gln88) of the BCL oxyanion hole are responsible for stabilizing the tetrahedral intermediate, which donate their backbone amide protons to the substrate in the transition state during ester hydrolysis . It was also demonstrated that interactions with the Leu17 residue contributes to the oxyanion hole narrowing, promoting different behaviors on the BCL enantioselectivity and substrate accessibility to the enzyme catalytic site .…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Leu17 is one of the two hydrogen‐bond donor amino acid residues that constitute the BCL oxyanion hole and stabilize the tetrahedral intermediate during catalysis. As described before, the two constituent's amino acids (Leu17 and Gln88) of the BCL oxyanion hole are responsible for stabilizing the tetrahedral intermediate, which donate their backbone amide protons to the substrate in the transition state during ester hydrolysis . It was also demonstrated that interactions with the Leu17 residue contributes to the oxyanion hole narrowing, promoting different behaviors on the BCL enantioselectivity and substrate accessibility to the enzyme catalytic site .…”
Section: Resultsmentioning
confidence: 76%
“…Furthermore, two amino acids (Leu17 and Gln88) close to the active site form the BCL oxyanion hole. These amino acids are responsible for stabilizing the tetrahedral intermediate, which through donate their backbone amide protons to the substrate in the transition state during ester hydrolysis . A detailed analysis through molecular dynamics simulations in different media (water, octane, and water/octane interface) was performed by Barbe et al The researchers investigate the movement of the BCL Lid Domain, showing that the Leu17 residue contributes to the oxyanion hole narrowing.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous features that make lipases useful biocatalysts for industry such as (i) broad substrate spectrum, (ii) excellent chemo-, regio-and stereoselectivity, (iii) high stability towards harsh reaction conditions, (iv) independence of cofactors and, furthermore, (v) a wide variety of lipases is commercially available [26]. Due to all these advantages lipases are used in industry for the removal of fats and oils or for the production of NEFA, monoacylglycerols (MAG), and diacylglycerols (DAG) as raw material [27].…”
Section: Lipasesmentioning
confidence: 99%
“…Lipases (EC 3.1.1.3, triacylclycerol acylhydrolases) are interfacial enzymes while catalysing the hydrolysis of lipids, and can also catalyse the esterification and transesterification under some favourable environments (Casas‐Godoy et al . ). Lipases have been widely used in food industry, oleochemical industry, detergent industry and pharmaceutical industry and some other fields (Goswami et al .…”
Section: Introductionmentioning
confidence: 97%
“…), due to their substrate specificities, substrate varieties and catalytic activities in both conventional and nonconventional media (Casas‐Godoy et al . ). Unfortunately, there are very limited lipases available for industrial application, mostly ascribed to their high production cost.…”
Section: Introductionmentioning
confidence: 97%